2011
DOI: 10.1089/gtmb.2010.0149
|View full text |Cite
|
Sign up to set email alerts
|

Social Stratification in the Sikh Population of Punjab (India) Has a Genetic Basis: Evidence from Serological and Biochemical Markers

Abstract: The present study revealed much genetic heterogeneity in differently ranking Sikh caste populations of Punjab, mainly attributable to their different ethnic backgrounds, and provided a genetic basis to social stratification present in this religious community of Punjab, India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…There is necessary to fill a big lacuna with information about the genetic diversity of Sikh Population. A very few number of genetic studies on Sikh population have been carried out around the world [16][17][18][19][20][21][22][23]. However, no STR marker based study on Sikh populations of central India has been reported in the literature till date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is necessary to fill a big lacuna with information about the genetic diversity of Sikh Population. A very few number of genetic studies on Sikh population have been carried out around the world [16][17][18][19][20][21][22][23]. However, no STR marker based study on Sikh populations of central India has been reported in the literature till date.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study 140 unrelated individuals of three studied Sikh population Arora (n=40), Ramgariha (n=50) and Jat (n=50) were taken for analysis from MP, India on the nine microsatellite loci which are D13S317 (13q22-31), D7S820 (7q11. [21][22], Amelogenin (X:p22.1-22.3;Y:p11.2), D2S1338 (2q35-37.1), D21S11 (21q11.2-q21), D16S539 (16q24-qter), D18S51 (18q21.3), CSF1PO (5q33. and FGA (4q28).…”
Section: Introductionmentioning
confidence: 99%